Percepción sobre el proceso de aprendizaje bajo el contexto de virtualidad en estudiantes de odontología - Soraluz-Alejo, Milagros (2023)
The objective of this article is to know the perception of dental students about their learning process under the context of virtuality. For this purpose, a search was carried out for scientific articles, review articles and theses published from 2020 to 2023. The databases from which the studies were compiled were: Pubmed/MEDLINE, Scopus, SciELO, and Google Scholar. The opinions of the students were mostly positive. The positive aspects of virtuality were related to the flexibility of schedules, time savings and extra expenses; They also indicated that it turns out to be a didactic way of carrying out the theoretical subjects. On the other hand, the negative aspects were linked to clinical and laboratory subjects; they indicated that their learning process during the pandemic was deficient in these subjects. However, some studies have shown that virtuality is a good complementary alternative for preclinical students, because it prepares them to approach the patient with greater confidence and security. It can be concluded that virtuality is a good ally in learning dental education; some of the students encourage this modality to continue over time, especially in theoretical and preclinical courses. Virtuality can continue to be part of dental education in our country, but it also depends on the teaching strategies and methodologies that accompany it.